2016
DOI: 10.1002/jbmr.2848
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Hypoxia Promotes Heterotopic Ossification by Amplifying BMP Signaling

Abstract: Hypoxia and inflammation are implicated in the episodic induction of heterotopic endochondral ossification (HEO); however, the molecular mechanisms are unknown. HIF-1α integrates the cellular response to both hypoxia and inflammation and is a prime candidate for regulating HEO. We investigated the role of hypoxia and HIF-1α in fibrodysplasia ossificans progressiva (FOP), the most catastrophic form of HEO in humans. We found that HIF-1α increases the intensity and duration of canonical bone morphogenetic protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(130 citation statements)
references
References 81 publications
8
122
0
Order By: Relevance
“…Interestingly, noting the critical roles of Hif1α on normal chondrogenesis, Agarwal et al also found that rapamycin decreased extraskeletal bone formation by inhibiting HIF1α in 3 HO mouse models (31). Also of note, the expression levels of HIF1α and several related downstream genes were not upregulated in FOP-iMSCs compared with resFOPiMSCs (Supplemental Figure 11), suggesting that the Hif1α pathway is not related to the Activin-A/FOP-ACVR1/mTOR signaling pathway in FOP-iMSCs, although hypoxia occurs during HO, as dis- cussed in several studies (31,32). Another important role of mTOR signaling is that of mediating inflammatory responses (74,75), which might have an impact during the early stages of FOP in vivo (73).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, noting the critical roles of Hif1α on normal chondrogenesis, Agarwal et al also found that rapamycin decreased extraskeletal bone formation by inhibiting HIF1α in 3 HO mouse models (31). Also of note, the expression levels of HIF1α and several related downstream genes were not upregulated in FOP-iMSCs compared with resFOPiMSCs (Supplemental Figure 11), suggesting that the Hif1α pathway is not related to the Activin-A/FOP-ACVR1/mTOR signaling pathway in FOP-iMSCs, although hypoxia occurs during HO, as dis- cussed in several studies (31,32). Another important role of mTOR signaling is that of mediating inflammatory responses (74,75), which might have an impact during the early stages of FOP in vivo (73).…”
Section: Discussionmentioning
confidence: 85%
“…The vast majority of drug candidates for FOP treatment suppress the abnormal activation of BMP signaling. Examples include direct kinase inhibitors of the catalytic domain of BMP type I receptors, such as dorsomorphin, LDN-193189, DMH1, RK-0071142, ML357, LDN-212854, and K0288, which consequently suppress the phosphorylation of the downstream effectors SMAD1/5/8 (22)(23)(24)(25)(26)(27); RARγ agonists, which reduce the expression of SMAD1/5/8 by protein degradation (28); allele-specific RNAi (ASP-RNAi) that target mutated ACVR1 (FOP-ACVR1) mRNA for degradation (29,30); inhibitors of hypoxiainducible factor-1α (HIF1α), which prevent the formation of mesenchymal condensations (31) or amplification of BMP signaling (32); and others (33,34). Among these drug candidates, only palovarotene (28,(35)(36)(37), a RARγ agonist, is now in clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…Predictably, the endochondral formation of traumatic HO is also dependent upon HIF-1α activity, and recent studies have leveraged this insight to use tissue hypoxia as a potential therapeutic target [19,83]. The recent work of Wang et al demonstrates that hypoxia induces retained expression of the mutated ACVR1 receptor in FOP patients through increased activity of Rabaptin-5 (RABEP1) [84]. In FOP lesions, predominating hypoxia ensures sustained expression and sensitivity of resident cells to hyperactive BMP signaling.…”
Section: Cell Signaling: Pathways Of Differentiation Growth and Promentioning
confidence: 99%
“…Generation of a hypoxic and inflammatory microenvironment in skeletal muscle is a critical step in the formation of HEO [17, 18]. HIF1-alpha integrates the cellular response to both hypoxia and inflammation and amplifies ligand-independent Smad 1/5/8 signaling in the presence of mtACVR1 [18].…”
Section: Targets and Strategies For The Prevention And Treatment Omentioning
confidence: 99%
“…HIF1-alpha integrates the cellular response to both hypoxia and inflammation and amplifies ligand-independent Smad 1/5/8 signaling in the presence of mtACVR1 [18]. Blocking HIF1-alpha pharmacologically with PX-478, apigenin, imatinib or rapamycin abrogates HEO in FOP mouse models [17, 18]. …”
Section: Targets and Strategies For The Prevention And Treatment Omentioning
confidence: 99%